1999
DOI: 10.1002/(sici)1097-4547(19990715)57:2<271::aid-jnr13>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent loss and proliferation of astrocytes following lateral fluid percussion brain injury in the adult rat

Abstract: Astrocyte populations were analyzed over a period of 1 month in the hippocampus following lateral fluid percussion (FP) brain injury. Rats (n = 23) were subjected either to a brain injury of moderate severity, or to anesthesia and surgery without injury (n = 7). At 3 days, 1, 2, or 4 weeks postinjury, subgroups of animals were sacrificed and the brains removed and sectioned for histochemical analysis. The density of astrocytes, identified with gold sublimate staining, decreased significantly in the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The development of glioblastoma multiforme following a traumatic cerebral contusion is possible [18]. There are several case reports in the literature that discuss posttraumatic gliomas [1][2][3][4][5][6][7][8][9][10][11][12], but some of these cases might only be a statistical coincidence. Hochberg et al [10] demonstrated that severe head injury is a significant risk factor for the development of glial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of glioblastoma multiforme following a traumatic cerebral contusion is possible [18]. There are several case reports in the literature that discuss posttraumatic gliomas [1][2][3][4][5][6][7][8][9][10][11][12], but some of these cases might only be a statistical coincidence. Hochberg et al [10] demonstrated that severe head injury is a significant risk factor for the development of glial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma initiates glial cell proliferation by triggering various growth factors that result in malignant neoplasms. Schiffer et al [23] detected astrocytic proliferation on the ipsilateral injury side in the rat brain two days after trauma, and astrocytic proliferation was demonstrated in regions of fluid percussion injury and deteriorated blood-brain barrier regions [9]. Kernie et al [12] demonstrated significant astrocyte and neural precursor proliferation in response to traumatic brain injury regions at 60 days after trauma, and Propiono bacterium acnes was isolated within the posttraumatic glioma tissue [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, the presented case show formation of GBM at the site of prior brain injury. 2,3,6,7,[9][10][11][12][13][14][15]18 Trauma and glial scarring are known to be predisposing factors for the development of malignant glial tumors. 25 The development of glioblastoma multiforme following a traumatic cerebral contusion is possible.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nerve growth factor (NGF) is increased at 3 days after TBI (Boockvar et al, 2005), and we previously found increased basic fibroblast growth factor (bFGF) and endothelial growth factor (EGF) expression levels at 2 days post-injury (unpublished data). After the regression of this acute phase of inflammation in the injured brain, astrocyte proliferation peaks at approximately 3 days post-TBI, followed by new microvasculature and glia limitans formation in the later stages postinjury (Hill-Felberg et al, 1999). Therefore, the injury response has an early and a late phase, each of which is characterized by its own distinct microenvironment.…”
Section: Discussionmentioning
confidence: 99%